Nasalance and nasality at experimental velopharyngeal openings in palatal prosthesis: a case study - Lima-Gregio, Aveliny Mantovan (2011)
The use of prosthetic devices for correction of velopharyngeal insufficiency (VPI) is an alternative treatment for patients with conditions that preclude surgery and for those individuals with a hypofunctional velopharynx (HV) with a poor prognosis for the surgical repair of VPI. Understanding the role and measuring the outcome of prosthetic treatment of velopharyngeal dysfunction requires the use of tools that allow for documenting pre- and post-treatment outcomes. Experimental openings in speech bulbs have been used for simulating VPI in studies documenting changes in aerodynamic, acoustic and kinematics aspects of speech associated with the use of palatal prosthetic devices. The use of nasometry to document changes in speech associated with experimental openings in speech bulbs, however, has not been described in the literature. Objective: This single-subject study investigated nasalance and nasality at the presence of experimental openings drilled through the speech bulb of a patient with HV. Material and Methods: Nasometric recordings of the word "pato" were obtained under 4 velopharyngeal conditions: no-opening (control condition), no speech bulb, speech bulb with a 20 mm(2) opening, and speech bulb with 30 mm(2) opening. Five speech-language pathologists performed auditory-perceptual ratings while the subject read an oral passage under all conditions. Results: Kruskal-Wallis test showed significant difference among conditions (p=0.0002), with Scheffe post hoc test indicating difference from the no-opening condition. Conclusion: The changes in nasalance observed after drilling holes of known sizes in a speech bulb suggest that nasometry reflect changes in transfer of sound energy related to different sizes of velopharyngeal opening.